2021
DOI: 10.3390/microorganisms9112363
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides from Bifidobacterium animalis Ameliorate Escherichia coli-Induced IPEC-J2 Cell Damage via Inhibiting Apoptosis and Restoring Autophagy

Abstract: Enteropathogenic Escherichia coli (EPEC) is a common zoonotic pathogen that causes acute infectious diarrhea. Probiotics like Bifidobacterium are known to help prevent pathogen infections. The protective effects of Bifidobacterium are closely associated with its secretory products exopolysaccharides (EPS). We explored the effects of the EPS from Bifidobacterium animalis subsp. lactis (B. lactis) on ameliorating the damage of an intestinal porcine epithelial cell line (IPEC-J2) during EPEC infection. Pretreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The higher survival of NCM460 cells in the exclusion experiment than that in competition experiments showed that the pre-exposure was helpful to B. subtilis LF11 to play obvious exclusive activity against Salmonella infection. Generally, these results are consistent with the reports that probiotics is known to help prevent pathogen infections in application (Que et al, 2021;Yuan et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The higher survival of NCM460 cells in the exclusion experiment than that in competition experiments showed that the pre-exposure was helpful to B. subtilis LF11 to play obvious exclusive activity against Salmonella infection. Generally, these results are consistent with the reports that probiotics is known to help prevent pathogen infections in application (Que et al, 2021;Yuan et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…43 Exopolysaccharides (EPS) secreted by probiotics can restore cell morphology, down-regulate the expression of cysteine aspartate specific proteinase (caspase), and promote the formation of autophagosomes to alleviate E. coli -induced cell apoptosis. 44 Surface layer proteins (SLP) of probiotics could protect HT-29 cells against intestinal pathogen-induced apoptosis through a mitochondria-mediated pathway. 45 Our work confirms the inhibitory effects of L. reuteri and the supernatant on E. coli -induced apoptosis in primary intestinal epithelium models.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research shows similar effects of bacterial-derived EPS. Notably, EPS from Bifidobacterium animalis improved cell growth in enteropathogenic Escherichia coli-damaged intestinal cells [ 40 ]. EPS produced by Streptococcus thermophilus and Lactobacillus plantarum also protect against intestinal epithelial monolayer disruption in colitis models [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%